2008
DOI: 10.1080/15374410802148129
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Internalizing Problems: Effects of Parental and Grandparental Major Depressive Disorder on Child Behavior

Abstract: Effects of lifetime histories of grandparental (G1) and parental (G2) major depressive disorder (MDD) on children's (G3) internalizing problems were investigated among 267 G3 children (ages 2-18 years) who received Child Behavior Checklist (CBCL) ratings and had diagnostic data available on 267 biological G2 parents and 527 biological G1 grandparents. Results indicated that G1 MDD conferred risk for G2 MDD, but not for G3 CBCL scores. G2 MDD predicted higher G3 Internalizing and Anxious/Depressed scores. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 57 publications
(67 reference statements)
5
52
1
Order By: Relevance
“…A number of studies suggest increased rates of depression among children of both mothers and fathers, as well as grandparents, with major depressive disorders, 29 with virtually all using small sample sizes. A recent metaanalysis of data from 28 studies revealed that paternal depression is associated with a significant decrease in positive paternal parenting practices, which may serve as a mechanism by which depression is transmitted between generations.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies suggest increased rates of depression among children of both mothers and fathers, as well as grandparents, with major depressive disorders, 29 with virtually all using small sample sizes. A recent metaanalysis of data from 28 studies revealed that paternal depression is associated with a significant decrease in positive paternal parenting practices, which may serve as a mechanism by which depression is transmitted between generations.…”
Section: Figurementioning
confidence: 99%
“…Similarly, the literature on the high concordance between mothers' and fathers' mental health and the transmission of depression within families might suggest that mental health problems in general, and depression in particular, when occurring in both mothers and fathers in the same family, is associated with even higher rates of child emotional or behavioral problems. [27][28][29] This article reports the findings of analyses conducted using a large, nationally representative sample of the US population to evaluate the following 3 hypotheses: first, that children of fathers with mental health problems and depressive symptoms have higher rates of emotional or behavioral problems; second, that the rates of such problems are lower among children with fathers who have mental health problems than among children with mothers with these problems; and third, that rates of emotional or behavioral problems are highest among children who have both mothers and fathers with mental health problems and depressive symptoms.…”
mentioning
confidence: 99%
“…The continuity of mental health and adjustment problems is not limited to two generations as it has been documented to occur at least across three generations [3][4][5][6][7][8][9][10][11]. However, a major unanswered question is whether the relationship between multiple mental health problems across generations is a result of the continuity of underlying problems that are genetically transmitted across generations, or is the result of gene-environmental interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Intergenerational studies have become of special interest, as heritable risk and early childhood biological markers of emotional disorder may be passed across consecutive generations (e.g., temperamental variables, elevated cortisol levels) [1,2]. In a like manner, psychosocial characteristics that increase the risk of emotional and conduct disturbances may be passed from parent to child via processes such as modeling and direct communications [3]. To the extent that these genetic, biological, and psychosocial characteristics-and their attendant risk-are transmitted from one generation to the next, an intergenerational mediation model may best characterize the development of psychopathology in general as well as for specific disorders (i.e., G1, G2, and G3).…”
Section: Introductionmentioning
confidence: 99%
“…31 (2), 2003) Interest in this kind of studies is that heritable risk and biological markers (e.g., temperamental variables, elevated cortisol levels) of emotional disorder that are identifiable in early childhood may be passed across consecutive generations (e.g., Ashman el al., 2002;Goldsmith, Buss, & Lemery, 1997). In a like manner, psychosocial characteristics that increase the risk of emotional disturbances may be passed from parent to child via processes such as modelling and direct communications (Pettit et al, 2008). To the extent that these genetic, biological, and psychosocial characteristics-and their attendant risk-are transmitted from one generation to the next, an intergenerational mediation model (i.e., G1 G2 G3) may best characterize the development of psychopathology in general as well as for emotional disorders.…”
mentioning
confidence: 99%